Microcalcification enhancement and classification on mammograms using the wavelet transform - Docusse, Tiago A. [UNESP]; Furlani, Jullyene R. [UNESP]; Romano, Rodolfo P. [UNESP]; Guido, Rodrigo C.; Chen, Shi-Huang; Marranghello, Norian [UNESP]; Pereira, Aledir S. [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2008)
This paper presents a method to enhance microcalcifications and classify their borders by applying the wavelet transform. Decomposing an image and removing its low frequency sub-band the microcalcifications are enhanced. Analyzing the effects of perturbations on high frequency subband it's possible to classify its borders as smooth, rugged or undefined. Results show a false positive reduction of 69.27% using a region growing algorithm. © 2008 IEEE.
Keywords: Wavelet transforms; False positives; High frequencies; Low frequencies; Microcalcification; Microcalcifications; Region growing algorithms; Sub bands; Neural networks